The Impact of Livelihood Capital on the Poverty Escaping of Poor and Near-Poor Households in Ninh Binh Province - Song, Nguyen Van; Diep, Nguyen Xuan; Nam, Nguyen Quang; Tra, Dao Thu; Man, Do Thi; Hao, Le Thi Thanh; Nam, Le Phuong; Huyen, Vuong Thi Khanh (Discoveries in Agriculture and Food Sciences, 2024)
-